The Effects of IoT on Sustainable Logistics Management Practices and Sustainability Performance in the Manufacturing Sector: A Comparative Study of Ghana and Indonesi - Gilbert Korku Akubia; Vanessa Gaffar; Mokh Adib Sultan; Denny Andriana (UIN Sunan Gunung Djati, 2024)
This study examines the impact of sustainable logistics practices—green transportation, waste management, energy efficiency, and sustainable packaging—on sustainability performance in the manufacturing sectors of Ghana and Indonesia, with a focus on the moderating role of Internet of Things (IoT) development. The research highlights the importance of both internal resources and external factors in achieving sustainability goals. Using a quantitative approach and a descriptive survey design, data were collected from 374 manufacturing firms in Ghana and 379 in Indonesia. The study employed a structured questionnaire and applied Ordinary Least Squares (OLS) regression to analyze the relationship between sustainable logistics practices, IoT growth, and sustainability performance. Sustainable logistics practices positively influence sustainability performance, with IoT moderating this relationship. Firms in Indonesia demonstrated higher performance due to advanced IoT infrastructure, while Ghana showed limitations due to less developed technological infrastructure. The findings emphasize the need for investment in IoT infrastructure to enhance the effectiveness of sustainable logistics practices, particularly in developing countries. The study contributes new insights into the moderating role of IoT in sustainability and offers practical guidance for policymakers and businesses. This study provides a novel cross-country perspective on how IoT development influences the effectiveness of sustainable logistics practices in emerging economies, bridging gaps in the existing literature on technology-driven sustainability strategies.